PENGARUH LATIHAN PUKULAN LOB DENGAN METODE PENGULANGAN TERHADAP KEKUATAN PUKULAN ATLET BULUTANGKIS CLUB BINA MUDA PEKANBARU - Nova, Fifit; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Issue in this research is about lob shot that often the shuttlecock reaches unexpected area or soar overhead due to weak shot or improper shot, and make theopponent will be easy to smash. Base on this issue writer give lob shot exercise with repetition method to determine an effect against the shot strength of badminton athlete Bina Muda Club Pekanbaru. This type of research is experiment with one group pretest ? posttest design. Populations on this research are 6 people badminton athlete Bina Muda Club Pekanbaru. The sampling technic used is purposive sampling where all the population sampled. The instrument performed for the shot power is clear test. After that the data was processed with statistic to test the normality with liliefors test at significant level ? (0.05). The hypothesis proposed is the influence of lob shot exercise with repetition method against the shot strength of badminton athlete Bina Muda Club Pekanbaru. From the analysis resulted pretest clear test with an average 56,17 and the average posttest of 70,83 with an increase of 88. Base on analysis t Test resulted tcount of 5,24 and ttable 2,015 it means tcount > ttable. Therefore there is effect of lob shot exercise with repetition against the shot strength of badminton athlete Bina Muda Club Pekanbaru.Key Words : Lob, Repetition Method